EFFECTIVENESS OF THE INNOVATION PORTFOLIO IN POLISH ENTERPRISES – RESEARCH RESULTS - Jurczak, Jolanta (Management and Administration Journal, 2024)
A single innovation project has a low probability of success, while the company’s chances of gaining a competitive advantage are low. Only a properly diversified innovation portfolio gives a chance for market success. The aim of the article is to analyze the issue of the effectiveness of innovation portfolio management in Polish enterprises, due to various external and internal factors, and also to identify clues determining the success of the innovation portfolio among enterprises in the future. For this purpose, a literature review in the area of the innovation portfolio was conducted. Also the method of analysis and criticism of the literature was applied. In the research process, empirical articles and Statistics Poland reports were analyzed. As a result of the analyses, effective ways to build innovation portfolio efficiency were identified by pointing out factors that can contribute to key optimization decisions (e.g., proper planning and diversification of the innovation project portfolio). Enterprises, in order to achieve innovation portfolio efficiency in difficult market conditions, should reallocate their resources to less risky innovation projects, and at the same time accepting the risks associated with introducing a transformational innovation.